The Role of Noninstrumental Justice and Age in Predicting Organizational Commitment: Evidence from Malaysia - Aizzat Mohd. Nasurdin (Gadjah Mada International Journal of Business, 2005)
The purpose of this paper is to determine the influence of the noninstrumental component of procedural justice on organizational commitment and whether this relationship is moderated by age. Regression analysis on a sample of 161 employees revealed that noninstrumental procedural justice had a significant effect on organizational commitment. The hypothesis concerning the role of age as a moderator was not supported. Implications for managerial practice and future research are discussed.